2013
DOI: 10.1111/jsm.12032
|View full text |Cite
|
Sign up to set email alerts
|

Habituation of Sexual Responses in Men and Women: A Test of the Preparation Hypothesis of Women's Genital Responses

Abstract: Introduction Laboratory studies have revealed two well-replicated sex differences in sexual arousal patterns: category specificity and sexual concordance. Men's genital responses are dependent on specific sexual cues and are concordant with subjective reports of arousal. Women's genital responses are much less dependent on specific sexual cues and are much less concordant with their subjective reports. The preparation hypothesis provides a functional explanation for these sex differences and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
4
23
2
Order By: Relevance
“…The results of the present study replicate those of Dawson et al (2013) in that the genital responses of men and women declined significantly and similarly as a result of repeated exposure to sexual stimuli. This pattern was robust to a variety of scoring methods.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the present study replicate those of Dawson et al (2013) in that the genital responses of men and women declined significantly and similarly as a result of repeated exposure to sexual stimuli. This pattern was robust to a variety of scoring methods.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, women appeared to be more sensitive to the subtle changes in the stimuli than men. This is consistent with the preparation hypothesis in that women more so than men should be aware of changes in stimuli, because Table 1 Effect Sizes ( 2 ) Associated With Habituation, Novelty, and Dishabituation Trials in Study 1 (Dawson et al, 2013) Note. 2 ϭ .01 (small), 2 ϭ .06 (medium), and 2 ϭ .14 (large) effect size values.…”
Section: Discussionsupporting
confidence: 82%
“…Studies of habituation to sexual stimuli in women and men demonstrate that genital [90][91][92][93][94][95][96] and subjective sexual arousal [90,91,[93][94][95][96] decline with repeated exposure to the same sexual stimulus, presumably because the hedonic quality associated with the stimulus changes as a function of repeated exposure. These studies also find that when novel stimuli are introduced, sexual arousal is restored [90][91][92][93][94][95][96]. Results from observational studies find a similar pattern; sexual desire can wane for both women and men in long-term relationships [56,57].…”
Section: Sexual Desire Across Timementioning
confidence: 98%
“…Previous studies have found evidence for sexual habituation in men. Male arousal, measured by penile tumescence, decreased upon repeated exposure to the same sexually explicit stimulus over shorter (i.e., less than 60 min; O'Donohue and Geer 1985; Plaud et al 1997;Koukounas and Over 2000;Dawson et al 2013) and longer time periods (i.e., 3-6 weeks; O'Donohue and Plaud 1994; Plaud et al 1997). In contrast, we did not find significant changes in any of the ejaculate parameters we measured between a man's first and sixth exposure to stimulus material involving the same actor and actress over an 11-14 day period.…”
Section: Discussionmentioning
confidence: 99%